Nicotine Dependence and Periodontal Status among Tobacco Users in a Dental Hospital of Kathmandu Valley - Dahal, Sirjana; Poudel, Prakash; Adhikari, Shradha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2020)
Introduction: Tobacco use in any form (smoking or smokeless) has been recognised to be a significant risk factor for the development and progression of periodontal disease. Objective: To assess the nicotine dependence and periodontal status among tobacco users of a dental hospital of Kathmandu Valley and determine their association. Methods: A cross-sectional study was conducted among 164 tobacco users visiting a dental hospital of Kathmandu. Nicotine dependence was assessed using the Fagerstrom Test for Nicotine Dependence-Smokeless Tobacco and the Fagerstrom Test for Nicotine Dependence. Their periodontal status was examined using community periodontal index and loss of attachment. Data were entered in Microsoft excel sheet and analysed in IBM SPSS Statistics for Windows, version 20. Mean, standard deviation, proportion, and percentage were calculated depending upon the nature of data. Chi-square test and Fisher’s exact test were used to determine the association between different variables. Results: Most of the tobacco smokers (34, 63.0%), chewers (12, 48.0%), and dual users (smoke=55, 64.7%; smokeless= 46, 54.1%) in this study showed low nicotine dependence. Majority of the tobacco users surveyed had periodontal pocket of 4-5 mm (73, 44.5%) and loss of attachment of 6-8 mm (79, 48.2%). Tobacco smokers and chewers having moderate or high nicotine dependence had periodontitis significantly higher than those who had low dependence. Conclusion: The findings in this study conclude that most of the individuals using tobacco in any form have periodontal diseases. Nicotine dependence is significantly associated with increased periodontal breakdown.